Partnership Management in Early Childhood Institutions - Nur Oktaviani, Mustika; Aslamiah, Aslamiah; Effendi, Rustam (Universitas Pahlawan Tuanku Tambusai, 2025)
Partnership management is one of the key aspects in the administration of Early Childhood Education (PAUD) institutions to improve the quality of educational services. This article aims to examine the strategies and implementation of partnership management between PAUD institutions and various stakeholders, including parents, the community, government, and the private sector. Using a qualitative approach through literature review and field observation, the study finds that effective partnerships are built on open communication, active participation from all parties, and a shared vision in supporting children's development. Furthermore, well-planned and sustainable partnership management has proven to strengthen institutional resources, expand program reach, and enhance community engagement. The findings of this study recommend the need for training PAUD managers in designing and managing strategic partnerships in a professional and ethical manner.